Local Wisdom and National Integration in Indonesia: A Case Study of Inter-Religious Harmony amid Social and Political Upheaval in Bunga Bondar, South Tapanuli - Rosmaida Sinaga; Flores Tanjung; Yuri Nasution (Journal of Maritime Studies and National Integration, 2019)
This study emphasizes on inter-religious affairs happened in Bunga Bondar, South Tapanuli began to experience turmoil when thenational movement era started in 1908 and itstillhappens to present-day. The Dutch colonial government advocated for inter-religiousharmony at a local level. The policy was pursued by the the Dutch colonial government out offear that the Indonesian people would developa sense of unity and fraternityamong them, thereby intensifying thespirit of nationalism. The Dutch government’s concern eventuallycame true when the power of the Christian wingof the national movement cooperated with itsIslamic counterpart. Along with the political upheavalsand social changes experienced by the Indonesian people, the harmony between religious groups in various regions was affected. Despite migration, changes of central and local leadership, and the flow of modernization that took place, the dynamics of inter-religious harmony of the 1930s are still present today.The tradition, the spirit of harmony, leadership models, and the application of local wisdom are all the key to the survival of inter-religious harmony in Bunga Bondar, South Tapanuli, as findings in research that can be used as a guide or model to build national integrity.